Metabolic Disorders and Diabetic Complications in Spontaneously Diabetic Torii Leprfa Rat: A New Obese Type 2 Diabetic Model. (25th February 2013) - Kemmochi, Yusuke; Fukui, Kenji; Maki, Mimi; Kimura, Shuichi; Ishii, Yukihito; Sasase, Tomohiko; Miyajima, Katsuhiro; Ohta, Takeshi
Abstract : Spontaneously Diabetic Torii Lepr fa (SDT fatty) rat, established by introducing the fa allele of the Zucker fatty rat into SDT rat genome, is a new model of obese type 2 diabetes. Both male and female SDT fatty rats show overt obesity, and hyperglycemia and hyperlipidemia are observed at a young age as compared with SDT rats. With early incidence of diabetes mellitus, diabetic complications, such as nephropathy, retinopathy, and neuropathy, in SDT fatty rats were seen at younger ages compared to those in the SDT rats. In this paper, we overview pathophysiological features in SDT fatty rats and also describe new insights regarding the hematology, blood pressure, renal complications, and sexual dysfunction. The SDT fatty rats showed an increase of leukocytes, especially the monocyte count, prominent hypertension associated with salt drinking, end-stage renal disease with aging, and hypogonadism. Unlike other diabetic models, the characteristic of SDT fatty rat is to present an incidence of diabetes in females, hypertension, and retinopathy. SDT fatty rat is a useful model for analysis of various metabolic disorders and the evaluation of drugs related to metabolic disease.